1997
DOI: 10.1248/bpb.20.704
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Neoglycolipids for Liposome Modification.

Abstract: We synthesized various glycolipid derivatives and examined the in vivo behaviors of liposomes modified with these novel glycolipid derivatives. Gal-t-psa (1,¿8-(2-hexadecyloctadecanoylamido)-3,6-dioxaoctyl¿-beta-D- galactoside), Lac-t-psa (3, 8-(2-hexadecyloctadecanoylamido)-3,6-dioxaoctyl beta-D-lactoside) and GalNAc-t-psa (4, 8-(2-hexadecyloctadecanoylamido)-3,6-dioxaoctyl 2-acetamido-beta-D-galactopyranoside) modified liposomes were recognized by the liver. Lac-t-psa (3) modified liposome was accumulated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The neoglycolipids were formed of Guerbet alcohol (G 28 ) directly bound to a sugar moiety (N-acetylglucosamine) or through a triethylene glycol (E 3 ) spacer (N-acetylglucosamine, ␣or ␤-fucose). The ␤-N-acetylglucosamine derivatives, GlcNAcG 28 (M w 613.97) and GlcNAcE 3 G 28 (M w 746.13), were synthesized according to the previously described route (Murahashi et al, 1997). The synthesis routes to fucose derivatives (M w 689.08) led either to the pure ␤-FucE 3 G 28 or to a mixture of the ␣and ␤-anomers (8.4:1.6), later referred to as ␣-FucE 3 G 28 in this paper (Faivre et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neoglycolipids were formed of Guerbet alcohol (G 28 ) directly bound to a sugar moiety (N-acetylglucosamine) or through a triethylene glycol (E 3 ) spacer (N-acetylglucosamine, ␣or ␤-fucose). The ␤-N-acetylglucosamine derivatives, GlcNAcG 28 (M w 613.97) and GlcNAcE 3 G 28 (M w 746.13), were synthesized according to the previously described route (Murahashi et al, 1997). The synthesis routes to fucose derivatives (M w 689.08) led either to the pure ␤-FucE 3 G 28 or to a mixture of the ␣and ␤-anomers (8.4:1.6), later referred to as ␣-FucE 3 G 28 in this paper (Faivre et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Also, Shimada et al (1997) showed that liposome surface-exposed galactose residues, attached to the distal end of a poly(ethylene glycol) chain anchored in the liposomal bilayer were effectively recognized by the galactose particle receptor on the Kupffer cells. In another work, by Murahashi et al (1997) it was reported that the recognition of neoglycolipid-bearing liposomes by liver cells took place. Apart from their ability to adsorb on a liposome surface and anchor to its bilayer membrane (Sancho et al, 1993), these neoglycolipids were found to be able to form supramolecular assemblies such as vesicles (Emmanouil et al, 1998;Blanzat et al, 1999), or nanoparticles formed of spherical sugar-persubstituted dendrimers (sugar balls) that exhibit a highly ordered structure with saccharide arrays on their periphery (Esumi et al, 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Shimada et al [68] have shown that liposome surface-exposed galactose residues, attached to the end of the poly(ethylene glycol) chain anchored in the liposomal bilayer were effectively recognized by the galactose receptor on the Kupffer cells. In another work, Murahashi et al [69] reported the recognition of neoglycolipidbearing liposomes by liver cells.…”
Section: Modeling Of Cellular Membrane Recognition Eventsmentioning
confidence: 98%
“…The lipid 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) was purchased from Avanti Polar Lipids (Alabaster, AL, USA). The neoglycolipid was formed of Guerbet alcohol (G 28 ) bound to a sugar (N-acetylglucosamine) through a triethylene glycol (E 3 ) spacer (N-acetylglucosamine) according to a previously described synthesis 35 (see Fig. 2).…”
Section: Lipids and Proteinsmentioning
confidence: 99%